The entrepreneurial arch : a strategic framework for discovering, developing and renewing firms - Faley, Timothy L., 1956- (Cambridge, United Kingdom : Cambridge University Press, 2015)
"The Entrepreneurial Arch is the result of my quest to pull all these pieces into a unified description of entrepreneurship. That description has two parts: Business Discovery and Business Execution. Each of those parts has three components. Together the six components describe fundamental skills that every organization wishes it could enhance: * Identify emerging opportunities (and threats) * Formulate innovative business solutions around those opportunities * Assess the feasibility of those proposed businesses * Develop an actionable implementation plan from disparate and incomplete information * Identify, align and/or acquire the necessary resources needed to power the plan forward * Drive accelerated growth"--
Includes bibliographical references (pages 286- 291) and index.
Keywords: Entrepreneurship; Business planning; New business enterprises; BUSINESS & ECONOMICS / Entrepreneurship